Vietnam Game Between USA and China - Pietrasiak, Małgorzata (International Studies. Interdisciplinary Political and Cultural Journal, 2018)
Vietnam tries to respond to changing international situations, while attempting to stay in accordance with its own ambitions. China and the USA, the two superpowers, are the most important partners of Vietnamese strategy, which is determined by these two countries. The most important economic partner and ideological ally is China. But both sides have some serious problems to resolve such as maritime disputes. The situation imposes the need to seek counterbalance, a reliable ally who provides protection for its own interests. So Vietnam looks to balance improved relations with China while seeking deeper and multidimensional relations with the USA. The United States offers many advantages that are attractive to Vietnam. Inevitably, economic ties and new projects e.g. TPP, political, cultural and scientific cooperation make up these advantages. However, the United States can only provide support for the Spratly and Paracel Islands’ dispute and improving cooperative measures in the South China Sea with the presence of U.S. naval vessels and dialogue that assists Vietnam defense. Vietnam has again become an element in the American strategy of pivoting to Asia.